2019
DOI: 10.1177/1099636219855322
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization for designing metallic corrugated core sandwich panels under air blast loading

Abstract: This research aims to improve the blast performance of trapezoidal corrugated core sandwich panel under air blast loading. A finite element model for the prediction of dynamic responses of trapezoidal corrugated core sandwich panel was first proposed and validated by experiments. Based on the simulation results, kriging models were established to approximate the relationships between design variables and blast performances, and correlation analyses were carried out to investigate the effects of the design vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The impact resistance increased due to high face to core attachment and load transfer capacities. Cai et al [91] examined the enhancement of a sandwich panel with a trapezoidal corrugated core, under the air blast loading condition. The study focused on achieving an optimal TZSP design that balances deformation response and energy absorption response under blast loading conditions The study revealed that the use of corrugated cores improved the overall performance of the plates.…”
Section: Corrugated Core Structurementioning
confidence: 99%
“…The impact resistance increased due to high face to core attachment and load transfer capacities. Cai et al [91] examined the enhancement of a sandwich panel with a trapezoidal corrugated core, under the air blast loading condition. The study focused on achieving an optimal TZSP design that balances deformation response and energy absorption response under blast loading conditions The study revealed that the use of corrugated cores improved the overall performance of the plates.…”
Section: Corrugated Core Structurementioning
confidence: 99%
“…Because of its lightweight structure, easy production, and excellent mechanical properties, sandwich panels are widely used in civil and military fields, including the aerospace, navigation, construction, and automation industries. For this purpose, researchers have investigated the response of sandwich panels under high-intensity dynamic loading and explored various core materials, including honeycomb cores [ 4 , 5 , 6 ], corrugated-core [ 7 , 8 , 9 ], porous foam materials [ 10 , 11 , 12 , 13 ], metal lattices [ 14 , 15 ], balsa wood [ 16 ], and others. Porous foam materials’ low density and weight make them an ideal choice for lightweight applications, effectively reducing the overall weight of structures and decreasing energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Kriging model allows for the generation of surrogate models, which can significantly reduce the computational cost associated with evaluating the mechanical response of lattice structures. 19 Du et al 20 implemented the optimization of the high-accuracy hierarchical Kriging model by using the hybrid optimization algorithm and applied the model to the structural dynamic optimization of rocket engines.…”
Section: Introductionmentioning
confidence: 99%